A Mini-Review on Plasma Technology for Hydrogen Productions towards the Transition of Net-Zero Economy from Biomass: The Key Operating Parameters - Raynard Christianson Sanito (CV Firmos, 2026)
During the last decades, the interest on the transition to net-zero economy, focusing on hydrogen (H2) energy, has emerged in an atmospheric-pressure microwave plasma reactor for converting biomass. Unfortunately, the obstacle of microwave plasma is the high energy consumption and proper selection of carrier gases. Thus, a better insight associated with microwave power set up is not only the main key to tackle these issues, but also is one of the primary factors to driving plasma technology forward. This mini-review paper identifies carrier gases, microwave power, flow rate and various issues as the most important points to produce high concentration of H2 as the possible gas in plasma technology systems. Also, it gives an insight about the conversion route of biomass to obtain the H2 and supporting the transition of net-zero economy. Economic issues are the main issues to implement the large-scale reactors, especially in energy consumption and carrier gases selection. Therefore, better understanding on operational parameters are required to develop the proper treatment to generate H2.